Carbono e nutrientes em solo sujeito à arenização com diferentes tipos de uso no bioma Pampa - Mendes, Lucas José (2023)
“Areais” are highly degraded areas resulting from natural and anthropic processes in the Rio Grande do Sul State (RS), Brazil. The loss of nutrients in the soil is the main factor that explains the great decrease or absence of vegetation in these areas. In addition to the possibility of economic use, forestry can be a viable alternative for the recovery and containment of the sands. However, there are no detailed studies on how fast-growing forest species can influence the edaphic conditions of sandynized soil. The objective of this study was to evaluate the soil and litter in a stand of Eucalyptus urophylla S.T. Blake after seven years of implantation in sandynized soil, comparing it with areas of “areal” and native grassland in the Pampa biome. The study was carried out at Horto Florestal Campo Laranjeira, belonging to the company CMPC, located in the municipality of Maçambará, RS, which has a humid subtropical climate with hot summers. Three study areas were selected: area with sandynized soil (AR), grassland (CP) and seven-year-old E. urophylla (EC). Three plots of 1,800 m² per study area were delimited and the collections of litter and soil were carried out randomly. Litter collections were performed at 81 points (nine points x three plots x three study areas). The litter was separated into fractions and dried in an oven to determine the dry biomass. Soil was collected in 36 trenches (four trenches per plot) at depths of 0-20 cm, 20-40 cm, 40-60 cm and 60-100 cm. The samples were dried and sent for analysis of the physical and chemical attributes of the soil. The determination of carbon (C) and nitrogen (N) in litter and soil was carried out in an elemental analyzer. Variables were submitted to analysis of variance (ANOVA) and compared using Tukey's test (p<0.05). Litter and its C and N stocks were higher in EC, followed by CP and AR areas. No differences were observed in soil physical attributes between AR and EC. Higher values of C, N, organic matter (OM), aluminum (Al), calcium (Ca) and magnesium (Mg) were found in CP soil. The establishment of eucalyptus improved the chemical quality of the soil, influencing the OM, C, pH, and Al. The sum of C stocks in litter and soil up to one meter depth is 55% higher in EC when compared to AR, however it is 25% lower when compared to CP.